Application of Swat Hydrological Model with GIS Interface to Upper Bernam River Basin - Lai, Sai Hin (2001)
Rising concern over the degradation of the environment due to rapid land development in recent years has created a need for watershed modeling. The Upper Bernam River Basin in South Perak and North Selangor, Malaysia was chosen for this study. This study was carried to evaluate the effectiveness of a GIS interface physically based hydrologic model (SWAT) in predicting surface runoff and sediment load from a basin scale watershed. The effects of land use changes on runoff and sediment loading rate were also studied. The data required for this study is the topographical, hydrometeorological, soil, and the land use data. All of them are integrated in a GIS in tabular, vector and grid formats. The land use data in this study were derived from Landsat TM images. These images were enhanced and classified using a combination of different classification strategies. The classified land use maps compares reasonably well with the map showing broad vegetation types of the river basin with an accuracy of 95%. Due to recent rapid land use changes, the model was run in a short term basis. The results from model application and statistical analysis show that SW AT generally does a good job in predicting both runoff flow and sediment load with a an average gap of 22% and 34% respectively between observed and predicted results. The exception is for those days with very heavy rainfall (> 35 mm/day), SWAT seriously overestimated runoff. Results from historical data, trend analysis, and calculated runoff rate and sediment loading rate due to open area have also shown the close relationship between surface runoff, sediment load and open area downstream of the upper river basin. It is found that the average increment of sediment loading rate for the study area ranges from 1.47 to 2.06 tonnes per millimeter of rainfall for each kilometer-square increase of open areas.